Development of Guided Inquiry Module using Canva Media to Enhance Critical Thinking and Motivation in Digestive System Learning - Siti Fatima; Elya Nusantari; Trisnawaty Junus Buhungo; Abdul Haris Odja; Frida Maryati Yusuf; Citron S. Payu (Universitas Muhammadiyah Mataram, 2025)
This study developed a guided inquiry-based learning module using Canva media to enhance critical thinking and learning motivation in Grade VIII students on the topic of the digestive system. Given the low science literacy and critical thinking skills in Indonesia, especially in junior high school science, this module aimed to address the gap in teaching abstract topics. A Research and Development (R&D) approach using the ADDIE model was applied in small-scale (10 students) and large-scale trials (55 students) at two junior high schools. Data were collected through expert validation, a critical thinking test, and a motivation questionnaire, analyzed using N-Gain and descriptive statistics. Results showed a moderate improvement in critical thinking (N-Gain of 0.63) and high student motivation (88% in the small-scale and 82% in the large-scale trial). The use of Canva within the inquiry-based approach significantly increased engagement and helped students understand abstract concepts, proving that combining inquiry-based learning with visual media is an effective strategy to improve critical thinking and motivation in junior high school science.